Natural and anthropogenic rates of soil erosion - Nearing, Mark A.; Xie, Yun; Liu, Baoyuan; Ye, Yu (International Soil and Water Conservation Research, 2017)
Regions of land that are brought into crop production from native vegetation typically undergo a period of soil erosion instability, and long term erosion rates are greater than for natural lands as long as the land continues being used for crop production. Average rates of soil erosion under natural, non-cropped conditions have been documented to be less than 2Mgha−1yr−1. On-site rates of erosion of lands under cultivation over large cropland areas, such as in the United States, have been documented to be on the order of 6Mgha−1yr−1 or more. In northeastern China, lands that were brought into production during the last century are thought to have average rates of erosion over this large area of as much as 15Mgha−1yr−1 or more. Broadly applied soil conservation practices, and in particular conservation tillage and no-till cropping, have been found to be effective in reducing rates of erosion, as was seen in the United States when the average rates of erosion on cropped lands decreased from on the order of 9Mgha−1yr−1 to 6 or 7Mgha−1yr−1 between 1982 and 2002, coincident with the widespread adoption of new conservation tillage and residue management practices. Taking cropped lands out of production and restoring them to perennial plant cover, as was done in areas of the United States under the Conservation Reserve Program, is thought to reduce average erosion rates to approximately 1Mgha−1yr−1 or less on those lands.